Analisa Propagasi Gelombang dalam Pandu Gelombang Optik Nonlinear dengan Medan Spatial Solitons - Harsoyono Harsoyono (Teknoin, 2005)
The  determination of field distribution of an electromagnetic wave propagating in an optically nonlinear planar waveguide with uniform medium is in priciple a two dimensional problem in the transverse plane. The associated generalized equation can be reduced to one-dimensional problems by means of effective index method, resulting in soliton like spatial distribution of the electric field along the transversal direction parallel to the waveguide plane. Taking into account this nonuniform field distribution in terms of the effective index of the guide, we have studied numerically the nonlinear coupling behaviors of a symmetric dual waveguide system. The result shows optically controlled waveguide coupling, the possibility  of implementing the optically controlled logic functions.  Keywords: nonlinear optic, spatial soliton, coupling effect.